Persepsi Masyarakat Lokal terhadap Keberdaan Situs-Situs Bersejarah dan Ketersediaan Amenitas dalam Pengembangan Wisata Pusat Kota Manado - Merryany Theovanny Bawole (HOSPITALITI DAN PARIWISATA, 2022)
The tourism industry is an industry that can provide a multiplayer effect, meaning that it can move all sectors and touch all elements in the structure of society. Tourism as a user of all available sectors, and it will not develop properly when the supply and support sectors are not running as they should. The link between the uniqueness of attractions and amenities such as hotels and restaurants is needed in tourism development, but sometimes it does not synergize well when tourism is developed. The purpose of this study was to examine the local community's perception of the existence of historical sites and amenities in the development of Manado Tua tourism. The method used is descriptive by conducting a survey of 100 respondents who are considered worthy of giving an assessment. The method of analysis is a normal percentage distribution. The results of the study found that in general the existence of historical sites and the availability of amenities such as hotels and restaurants were in good condition and provided positive support in the development of Manado's old city tourism.